Loss Aversion in the Laboratory - William G. Morrison; Robert J. Oxoby (Institute for the Study of Labor (IZA), 2014)
We report the results of a laboratory experiment testing for the existence of loss aversion in a standard risk aversion protocol (Holt and Laury, 2002). In our experiment, participants earn and retain money for a week before using it in an incentivized risk preference elicitation task. We find loss aversion, distinct from risk aversion, has a significant effect on behavior resulting in participants requiring higher compensation to bear risk.
Keywords: C91; D91; 330; risk aversion; loss aversion; experiments